The effect of Caffeine ingestion on neutrophil oxidative burst responses following prolonged cycling - Walker, G. J.; Caudwell, P.; Dixon, N.; Bishop, N. C. (International Journal of Sport Nutrition and Exercise Metabolism, 2006)
This study investigated the effect of caffeine ingestion on neutrophil oxidative burst responses to prolonged cycling. In a two part study, 19 endurance trained male cyclists (Part A - 11; Part B - 8) performed 90 min of exercise at 70% VO2max 1 h after ingesting 6 mg/kg body mass of caffeine (CAF) or placebo (PLA). CAF ingestion had no effect on the PMA-stimulated oxidative burst response (Part A), yet it attenuated the exercise-induced decline in f-MLP stimulated response that occurred with PLA (Part B). CAF ingestion significantly increased serum caffeine concentration and plasma adrenaline concentration following exercise. In addition, circulating lymphocyte count was increased following CAF ingestion whereas there was no effect on neutrophil number. Therefore, although CAF ingestion was associated with an increase in adrenaline, this was not associated with an expected decrease in neutrophil function. This suggests that in the present study, CAF ingestion influenced neutrophil function via alternative mechanisms.